(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In the modern world, the relevance of clean housing, premises and workplaces is more than ever a priority for the majority of the population, which is why the development of less aggressive household chemicals and their safe use currently has valuable weight. In this article we will analyze the use of chemically toxic substances in our lives, in particular its effect on the human body. We will also consider research and experiments conducted to study the safe concentration and composition of the cleaning product, including treatment methods in the event of pathogenic processes occurring upon contact with household chemicals.